Domain-Specific Views on Aging and Preparation for Age-Related Changes—Development and Validation of Three Brief Scales. (8th May 2018) - Kornadt, Anna E; Hess, Thomas M; Rothermund, Klaus
Abstract: Objectives: We developed brief versions of our questionnaires to assess domain-specific views on aging (age stereotypes and future self-views) and preparation for age-related changes. Methods: The brief scales were validated in an online study with N = 301 participants aged 23–88 years. Results: Mean values across domains show a differentiated picture for all 3 constructs, yielding evidence for the multidimensionality of views on aging and preparation for age-related changes. Rating profiles for the brief versions were similar to the long versions of the questionnaires, attesting to the equivalence of the brief and long scales. Within-domain correlations between the 3 constructs were also higher than between-domain correlations, further substantiating the claim of domain-specificity with regard to the predictive validity of the brief scales. Discussion: The new brief versions of the scales can be recommended for a differentiated assessment of views on aging and preparation for age-related changes when short forms of measurement are required.